Lung cancer incidence in young women vs. young men: A systematic analysis in 40 countries. Issue 3 (5th February 2020) - Fidler‐Benaoudia, Miranda M.; Torre, Lindsey A.; Bray, Freddie; Ferlay, Jacques; Jemal, Ahmedin
Abstract : Previous studies have reported converging lung cancer rates between sexes. We examine lung cancer incidence rates in young women vs . young men in 40 countries across five continents. Lung and bronchial cancer cases by 5‐year age group (ages 30–64) and 5‐year calendar period (1993–2012) were extracted from Cancer Incidence in Five Continents . Female‐to‐male incidence rate ratios (IRRs) and 95% confidence intervals (95%CIs) were calculated by age group and birth cohort. Among men, age‐specific lung cancer incidence rates generally decreased in all countries, while in women the rates varied across countries with the trends in most countries stable or declining, albeit at a slower pace compared to those in men. As a result, the female‐to‐male IRRs increased among recent birth cohorts, with IRRs significantly greater than unity in Canada, Denmark, Germany, New Zealand, the Netherlands and the United States. For example, the IRRs in ages 45–49 year in the Netherlands increased from 0.7 (95% CI: 0.6–0.8) to 1.5 (95% CI: 1.4–1.7) in those born circa 1948 and 1963, respectively. Similar patterns, though nonsignificant, were found in 23 additional countries. These crossovers were largely driven by increasing adenocarcinoma incidence rates in women. For those countries with historical smoking data, smoking prevalence in women approached, but rarely exceeded, those of men. In conclusion, the emerging higher lung cancer incidence rates in young women compared to young men is widespread and not fully explained by sex differences in smoking patterns. Future studies are needed to identify reasons for the elevated incidence of lung cancer among young women. Abstract : What's new? Lung‐cancer rates among women and men have been converging. In this international study, the authors found that, while lung‐cancer rates have declined among younger men, they are rising among younger women, despite the fact that these women are not smoking more than men. Adenocarcinoma appears to account for much of this increase. These findings forewarn of a higher lung‐cancer burden among women in the future, especially in higher‐income settings. Further work is needed to intensify anti‐tobacco strategies, and also to identify other factors causing the higher incidence burden among younger women.